INTERNATIONAL EXPERIENCE IN PROCESSING AND ASSESSMENT BY REGULATORY AUTHORITIES OF TRANSFER PRICING RISKS - KURILOV, YEVHEN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes and summarizes the international experience of regulatory authorities in dealing with transfer pricing risks as one of the basic elements of tax control over taxpayers' compliance with transfer pricing rules.An efficient process for processing and assessing transfer pricing risks helps to ensure quality selection and increase the effectiveness of audits of controlled transactions, increase the efficiency of the use of limited resources, as well as greater tax certainty and reduce the number of unreasonable audits.As a result of the study: international experience was summarized and an indicative process of processing and assessing transfer pricing risks was determined; the main points of the general approach to the issue of transfer pricing risks, which are currently used in practice by the regulatory authorities of economically developed countries, have been identified; the principles of transfer pricing risk management were determined and the importance of carrying out transfer pricing risk assessment processes on an ongoing and systematic basis was indicated; the approaches to organizing the processing and risk assessment of transfer pricing proposed by the specialists of the OECD, JTPF and the UN are considered.Also, the author of the article proposed to supplement this process with a fifth post-assessment stage, which should include the following three steps (13–15): internal inspection and quality control of risk assessment processes based on the results of transfer pricing audits; improving the list of transfer pricing risk indicators and descriptions of their features and identification methods; training and professional development of specialists in the assessment of transfer pricing risks. In addition, attention was drawn to the need for proper documentation of the processing and risk assessment of transfer pricing.The article also concludes that the processes of processing and assessing transfer pricing risks should be integrated into the processes that are carried out within the framework of the functioning of the general risk management system of both the tax authority and any modern large enterprise (group of enterprises).
Keywords: transfer pricing; tax control; transfer pricing risks; controlled operations; arm's length principle